Arhata pravacana - Cainasukhadāsa, 1900-1969.; Jainavidyā Saṃsthāna (Śrīmahāvīrajī, India) (Śrīmahāvīrajī, Rājasthāna : Jainavidyā Saṃsthāna, 2001)
Selections from Jaina canonical texts.
Mode of access: Internet.
Hindi and Prakrit.
Keywords: Jainism